Feeding and management practices in the New Zealand sport horse industry : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science at Massey University, Manawatu campus, New Zealand - Ferguson-Wilson, Millicent (Massey University, 2021)
Nutrition is a vital component of sport horse performance, ensuring they have sufficient energy to maintain condition as well as perform the demands of their sport. Nutrition as it concerns specifically to sport horses in New Zealand is a neglected topic of research. The aim of this paper was to describe the feeding practices and supplement use in New Zealand horses competing in the disciplines of dressage, eventing, show jumping, showing, western riding, and within pony club events. Data were collected via an online survey using Qualtrics Survey Software, obtaining a total of 364 valid responses, which could be taken to be an accurate distribution of the national herd, based on discipline and demographics. The overall mean bodyweight of horses in the survey was 540.7 kg, with horses involved in dressage, eventing, and show jumping tending to be heavier than other disciplines, and dressage horses being the heaviest overall. Overall mean ideal body condition score was 5.4, with showing and western horses having a significantly higher ideal BCS, at 5.9. Many (65.5%) of the horses had continuous access to pasture, with little variation between disciplines. Pasture management was typically rotational grazing, with a mean paddock size of 1.0 Ha. Pastures were most commonly ryegrass & clover, as is expected with New Zealand pastures, however many respondents (32.4%) were unsure what pasture type was sown on the grazing property. Horses were usually offered concentrates twice a day, however concentrates were only offered to most pony club horses once per day. Most (90.3%) responders fed hay in addition to the pasture that was grazed, and 80.9% fed concentrates. The mean quantity of concentrates fed per day was 1.9 kg as fed, with no difference between disciplines. The mean digestible energy supply per day was 81.8 MJ (range 0 - 369.5 MJ), with little variation between disciplines. This accounted for approximately 80% of the horse’s daily DE requirement, with the remainder assumed to be consumed from pasture. Many (89%) respondents reported the addition of dietary supplements into their horse’s daily ration. The most popular supplements fed were salt, bone and joint, mineral/vitamin balancer, digestion aid, and toxin binders. Important future research would be to quantify nutrient profile trends for all major nutrients in sport horse diets, and to quantify pasture intake and include it in nutrient profiles.
Keywords: 300303 Animal nutrition